Block copolymer concentration gradient and solvent effects on nanostructuring of thin epoxy coatings modified with epoxidized styrene-butadiene-styrene block copolymers - Ramos, José Angel (2012)
The gradient on block copolymer concentration through film thickness as well as the effects of casting solvents used on the nanostructuring of a thermosetting epoxy coating modified with an epoxidized poly(styrene-b- butadiene-b-styrene) (SBS) triblock copolymer was studied by means of atomic force microscopy and attenuated total reflectance infrared spectroscopy. Thin coating films based on a commercial epoxy-amine formulation consisting of diglycidyl ether of bisphenol A and a low-temperature fast curing amine were modified with several amounts of epoxidized SBS triblock copolymer. Toluene and a mixture of tetrahydrofuran and N,N-dimethylformamide were used as casting solvents. With epoxidation degrees higher than 45 mol % of polybutadiene block nanostructuring was achieved. Fast curing rate of the epoxy/amine system and the comparatively slow evaporation rate of the casting solvent led to a gradient of morphologies through the film cross section owing to the coalescence of small micelles into larger micellar domains in the case of low block copolymer content. For these reasons, different morphologies were also obtained in the midtransverse section of a film with variable thickness. Finally, pseudolamellar nanostructure at high copolymer contents was achieved as confirmed by parallel and perpendicular cuttings to the air/polymer interface. © 2012 American Chemical Society.